Leveraging Synergies from Integrative Land-Biodiversity-Climate Action for Improving Monitoring, Reporting, and Investments into Land Restoration in Uzbekistan - Economics of Land Degradation Initiative (Economics of Land Degradation initiative, 2025)
This concise brief targets policymakers, summarizing the key messages of the Uzbekistan case study. It highlights that land degradation has cost the country around USD 3 billion and outlines integrated investment strategies aligned with LDN, NDCs, and NBSAPs. The brief promotes the adoption of synergistic MRV systems and public-private finance mechanisms for more efficient land restoration.